Precise preoperative diagnosis of struma ovarii with pseudo-Meigs' syndrome mimicking ovarian cancer with the combination of 131I scintigraphy and 18F-FDG PET: case report and review of the literature - Sayaka Fujiwara; Hideaki Tsuyoshi; Toshiya Nishimura; Nozomu Takahashi; Yoshio Yoshida (BMC, 2018)
Abstract Background Struma ovarii is a rare ovarian neoplasm that often appears malignant on conventional imaging. Pseudo-Meigs' syndrome with ascites, pleural effusion, and elevated serum CA 125 levels is much rarer and leads to misdiagnosis of ovarian cancer and unnecessary extended surgery. Case presentation A 50-year-old woman with abdominal distention and dyspnoea was referred to our hospital. Ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI) showed a polycystic ovarian tumor with a solid component, pleural effusion, and massive ascites with negative cytology. Her serum CA 125 level was 1237 U/ml, indicating the presence of ovarian cancer. Based on increased uptake of 131I but no uptake of 18F-FDG in the tumor, the preoperative diagnosis was struma ovarii with pseudo-Meigs' syndrome, which was confirmed histologically. She had no evidence of ascites and pleural effusion six months after surgery. Conclusions To date, there have been no systematic reviews focused on preoperative diagnosis with imaging modalities. The combination of 131I scintigraphy and 18F-FDG PET/CT in addition to conventional imaging modalities can provide the precise preoperative diagnosis of struma ovarii with pseudo-Meigs' syndrome mimicking ovarian cancer, leading to the appropriate treatment strategy.